Spatial distribution and urban–rural disparity of unmet need for family planning among married/in-union women in Ethiopia: a spatial and decomposition analysis - Kebede, Shimels Derso; Mamo, Daniel Niguse; Adem, Jibril Bashir; Walle, Agmasie Damtew; Tsega, Yawkal; Addisu, Elsabeth; Tadese, Zinabu Bekele; Enyew, Ermias Bekele (Frontiers in Reproductive Health, 2024)
BackgroundHigh unmet need for family planning combined with other factors, such as high early marriage and teenage pregnancy, increases the risk of developing obstetric fistula and other complications. This study aimed to assess spatial distribution and urban–rural disparities of unmet need for family planning among married/in-union women in Ethiopia.MethodsThe study was conducted on secondary data from a cross-sectional survey that was conducted nationally between September and December 2019 using a two-stage cluster design on a total of 265 enumeration areas. A total weighted sample of 5,349 married/in-union women was included in the analysis. ArcGIS Pro and SaTScan software were used to handle spatial analysis. Finally, multivariable decomposition analysis via a logit model was used to decompose the observed difference in unmet need by the compositional difference and the difference in effects of explanatory variables between places of residence.ResultsSpatial distribution of unmet need for family planning was clustered in Ethiopia with a global Moran's I index value of 0.25 (p-value = 0.004). Accordingly, enumeration areas in West Hararge, Arsi, Bale, Gujji, Borena, Jimma, and East Wellega zones of Oromia region, and Gurage, Hadiya, Silte, Gedio, Sidama, Wolaita, Alaba, and Dawro zones of South Nation and Nationality People region, and the southern part of Zone 3 in Afar region were detected as hotspot areas. The decomposition results revealed that there is a significant disparity in unmet need between urban and rural resident women (0.074, p-value < 0.001). Endowment and coefficient factors accounted for the urban–rural disparity, contributing 68.32% and 31.68%, respectively. Household size, husband’s opinion of family planning, community acceptance of family planning, woman’s age at first sexual intercourse, and the woman's age were key determinants of the urban–rural disparity.ConclusionThe results revealed a significant disparity in the unmet need for family planning based on place of residence, with a clustered spatial distribution across the study area and notable hotspot areas. Thus, targeted interventions should focus on mobilizing resources to high-risk areas and addressing the needs of high-risk groups to reduce the observed variation.